Implementasi Metode Tafsir Maudhu’i dalam Prinsip Pola Makan Sehat dan Gizi Seimbang - Arifandi, Firman; Endy, Endy Muhammad Astiwara (Majalah Sainstekes, 2024)
It is extremely hoped that the Qur'an can be the main solution in answering all issues throughout the ages. To fulfill these expectations requires the formulation of new thoughts regarding the methods used in interpreting the Koran, which are currently believed to be the best solution for every new issue or problem. This new method is now known as the maudhu'i tafsir method or thematic tafsir. This research aims to see to what extent the verses of the Al-Qur'an using the Maudhu'i interpretation approach talk about healthy eating patterns and the nutritional content of food that humans need in accordance with the perspective of health science. Humans need various types of nutrition to maintain their health and immune system. The source of nutritional intake is generally obtained through food. The method used in this research is qualitative research using a Maudhu'i interpretation approach strengthened by other literature studies such as books, journals, encyclopedias, documents, and so on. The results of the research show that there are several verses in the Al-Qur'an which, when viewed from a health science approach, are connected to healthy eating patterns and fulfilling human nutritional needs ranging from carbohydrates, protein, minerals, and other.